Sarcopenia is associated with increased hip fracture risk among middle-aged and elderly Chinese adults in longitudinal analysis of CHARLS data - Sensen Huang; Le Chang; Zhenyu Cai (Scientific Reports)
Abstract To investigate the temporal association between sarcopenia and hip fracture risk among middle-aged and elderly Chinese adults, given the rising prevalence of sarcopenia and increasing burden of hip fractures in aging populations. This longitudinal study analyzed data from 7775 participants aged ≥ 45 years in the China Health and Retirement Longitudinal Study (2011–2020). Sarcopenia was assessed based on muscle strength, mass, and physical performance. Hip fracture incidents were collected through follow-up interviews. Covariates included demographic characteristics, lifestyle factors (smoking, alcohol consumption), and chronic diseases (hypertension, diabetes, arthritis). Competing risk analysis and multiple logistic regression models were employed to evaluate the association between sarcopenia and hip fracture risk. At baseline, 1436 (18.5%) participants had sarcopenia. The sarcopenia group showed higher hip fracture incidence than the non-sarcopenia group ((7.17% vs. 3.75%, P < 0.001). Cumulative incidence analysis revealed progressively widening disparity in fracture incidence between groups over the 9-year follow-up. After adjusting for multiple confounders, sarcopenia remained independently associated with increased hip fracture risk (adjusted OR = 1.33, 95% CI: 1.00–1.77, P = 0.0498). Sarcopenia serves as an independent risk factor for hip fracture among middle-aged and elderly Chinese adults, emphasizing the importance of early sarcopenia identification and prevention strategies.